2002
DOI: 10.1080/mmy.40.4.383.386
|View full text |Cite
|
Sign up to set email alerts
|

High rate of vaginal infections caused by non-C. albicans Candidaspecies among asymptomatic women

Abstract: A prospective observational study of patients attending a gynecological clinic and those referred to a clinic for genitourinary infections was undertaken with the purpose of evaluating the relative prevalence of non-C. albicans Candida species among Candida isolates from the vagina in different clinical settings in an area with high occurrence of vulvovaginal candidiasis. The rate of non-C. albicans Candida species was 44.5% among asymptomatic women, 19.4% among those with sporadic vaginitis and 21% among pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 17 publications
1
8
1
Order By: Relevance
“…The mentioned results were in contrast with those reported by Dan et al (2002) [32], who showed proteinase activity in 34 (85.0%) Candida isolates; this rate reached 100% in non- C. albicans species. In another study by Sachin et al (2012), proteinase production was found in 65 (59.1%) Candida isolates [33].…”
Section: Discussioncontrasting
confidence: 94%
“…The mentioned results were in contrast with those reported by Dan et al (2002) [32], who showed proteinase activity in 34 (85.0%) Candida isolates; this rate reached 100% in non- C. albicans species. In another study by Sachin et al (2012), proteinase production was found in 65 (59.1%) Candida isolates [33].…”
Section: Discussioncontrasting
confidence: 94%
“…Of the NAC species, C. glabrata is regarded as the second leading cause of VVC (~8% of cases), while C. krusei, C.parapsilosis, and C. tropicalis make up a majority of the remainder [18][19][20]. Vaginal symptoms resulting from infection with NAC species are often reported as being milder than those experienced during VVC caused by C. albicans [21]. However, inherent resistance to the azole drug class, as well as acquired resistance mechanisms, can complicate treatment of the NAC species [22,23].…”
Section: Pathology and Epidemiology Of Vulvovaginal Candidiasismentioning
confidence: 99%
“…Of these, C. glabrata is most frequently reported as the second leading causative agent (ϳ5%), and the remainder are most commonly composed of C. krusei, C. parapsilosis, and C. tropicalis (11,20,23). Reported vaginal symptoms caused by NAC species are often milder than those experienced during infection with C. albicans (26). However, antifungal resistance and recurrence rates are typically higher with the NAC species, necessitating prolonged and/or alternative treatment options (23,27).…”
mentioning
confidence: 99%